An in silico—in vitro Pipeline Identifying an HLA-A*02:01+ KRAS G12V+ Spliced Epitope Candidate for a Broad Tumor-Immune Response in Cancer Patients - Mishto, Michele; Mansurkhodzhaev, Artem; Ying, Ge; Bitra, Aruna; Cordfunke, Robert A.; Henze, Sarah; Paul, Debdas; Sidney, John; Urlaub, Henning; Neefjes, Jacques; Sette, Alessandro; Zajonc, Dirk M.; et al. (Frontiers in Immunology, 2019)
Targeting CD8+ T cells to recurrent tumor-specific mutations can profoundly contribute to cancer treatment. Some of these mutations are potential tumor antigens although they can be displayed by non-spliced epitopes only in a few patients, because of the low affinity of the mutated non-spliced peptides for the predominant HLA class I alleles. Here, we describe a pipeline that uses the large sequence variety of proteasome-generated spliced peptides and identifies spliced epitope candidates, which carry the mutations and binds the predominant HLA-I alleles with high affinity. They could be used in adoptive T cell therapy and other anti-cancer immunotherapies for large cohorts of cancer patients. As a proof of principle, the application of this pipeline led to the identification of a KRAS G12V mutation-carrying spliced epitope candidate, which is produced by proteasomes, transported by TAPs and efficiently presented by the most prevalent HLA class I molecules, HLA-A*02:01 complexes.